Interurban collective transport and road crashes in Santiago, Cape Verde - Horta,Gerard (2013)
Based on research first begun in Praia (capital of Cape Verde) into the new public organization of its streets and squares - increasingly occupied by cars and other types of motor vehicles -, this article develops a description of the social universe of private group transport on the island of Santiago, and analyses its relationship with road crashes. Its chief focus is the hiace, a generic term designating transportation vans in Cape Verdean society (although they are named after the Hiace model manufactured by Toyota, in this research the word is used as an emic concept). Thus, through the field work completed to date, it outlines the social processes and dimensions in which road crashes involving hiaces take place. Moreover, it puts forward some comprehensive explanations of the causes for the islands high road accident rate within the context of the urban transformation processes underway there. It furthermore reflects on the antagonistic experiences caused by the use of space by both motor vehicle drivers and the pedestrians themselves - space being understood as a social process - in relation to the living conditions and different experiences of the people of Cape Verde.